Safety and recommendation of voriconazole for invasive pulmonary aspergillosis in severe liver disease patients: a retrospective cohort study - Xin Zhang; Caopei Zheng; Ling Zhang; Yuqing Sun; Ying Liang; Xue Chen; Lijun Pang; Yulin Zhang (BMC Infectious Diseases)
Abstract Background Invasive pulmonary aspergillosis (IPA) is a common opportunistic infection in patients with severe liver disease (SLD), which increases the mortality of patients. The aim of this study was to evaluate the efficacy and safety of voriconazole for IPA in patients with SLD and explore an optimal antifungal regimen. Methods This was a retrospective cohort study of SLD patients diagnosed with proven or probable IPA at Beijing Youan Hospital, Capital Medical University between January 1, 2012 to January 31, 2023. Univariate and multivariate logistic regression analysis were performed to identify the impact of voriconazole on outcomes of SLD patients with IPA. Results A total of 142 patients were enrolled and categorized into voriconazole group (n = 92), echinocandins group (n = 26) and a combination of voriconazole and echinocandins group (n = 24). The 28-day all-cause mortality was lower in voriconazole group compared to the other groups (p = 0.033). Voriconazole monotherapy was associated with lower short-term mortality (OR 0.223, 95%CI 0.070–0.650, p = 0.008) and did not seem to exacerbate hepatic function deterioration in SLD patients with IPA (OR 0.259, 95%CI 0.094–0.674, p = 0.007) when compared to echinocandins monotherapy. Among the three subgroups of voriconazole monotherapy, no-loading dose regime demonstrated a superior response to IPA therapy compared to the standard-dose regimen (OR 0.264, 95%CI 0.068–0.845, p = 0.035). Conclusion Voriconazole monotherapy demonstrated good tolerability with lower mortality in SLD patients with IPA. A no-loading dose voriconazole regimen is proposed for IPA treatment in SLD patients, yet pharmacokinetic studies combined with prospective studies are needed for further validation.